Tingkat Partisipasi Masyarakat Lokal Dalam Pengembangan Kampung Wisata Kreatif Dago Pojok di Kota Bandung - Agnes Anggi Hasian Silaban; Gde Indra Bhaskara (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
A creative tourism is a form of sustainable tourism that offers authentic experiences of local culture. Tourism activities that have been running for about 9 years in Dago Pojok Creative Village, sparked researchers attention identify the condition of tourism and measuring level of local community participation in the development of Dago Pojok Creative Tourism Village. This study aims to identify tourism conditions and level of participation of local communities in the development of Dago Pojok Creative Tourism Village. The types of data used are qualitative and quantitative data with observation, interview and document data collection. Analysis of the data used is descriptive-qualitative data analysis using the concept of tourism components and the theory of a ladder of citizen participation. The results of this study show that the condition of tourism which is reviewed through the components of tourism products (4A) in Dago Pojok Creative tourism village recently is sufficient enough to improve some of the existing facilities. The level of community participation in Dago Pojok Creative Tourism Village is at the first level in the theory of a ladder of citizen participation. Based on the results, local communities have participated in the development of tourist attractions neverheless but it is still constrained by the government who expects the community itself to develop the tourist village without government assistance. On the contrary, local people expect assistance from the government. Keyword: participation, rate, community, creative, village